Comminution of biogenic materials. (13th February 2017) - Eisenlauer, Moritz; Teipel, Ulrich
Abstract: Renewable resources have been gaining increasing importance for energy generation in recent years. Lignocellulosic biomass, as an alternative to limited crude oil, can be utilized to produce these chemicals. The upstream process of comminution is a key element in the use of renewable raw materials. However, comminution is a highly energy consumptive process, making it necessary to assess the benefits of fine comminution in terms of reducing energy consumption by an adequate characterization of the products. The key factors to increased energy efficiency are, besides the mill type and the mill operation factors, the species of the renewable resource, in terms of water content and the mechanical properties which are the dominant factors in biomass size reduction. A better understanding of these interdependencies can help to improve the adjustment of particle size distribution and particle shape. As well as the total specific surface area and the energy demand for the comminution process, which impacts the overall efficiency of the supply chain process, disintegration, and the conversion. This work, therefore, focuses on the comminution of woody biomass in a cutting mill. It reports the effects of the influencing parameter of the biomass on the comminution process, the energy consumption, and the physical properties of the products regarding their particle size. Furthermore, selected experiments have been carried out on a swing hammer mill to compare the influence of the type of stressing.